PENGEMBANGAN COMPACT DISK (CD) INTERAKTIF MENGGUNAKAN MACROMEDIA FLASH PADA MATERI KUBUS UNTUK SISWA KELAS VIII SMP/MTs - Sumarni, Pipin - (Pendidikan Matematika, 2014)
This research aims to make learning interactive CD media with a valid and practical.Development Model used is a 4-D.development model comprises of 4 stages include: define,design, develop, and disseminate.This research was only done to the development stage.The development  phase was done only at the stage of validation and the practicalities of an interactive CD.Validation was  performad by two lectures of mathematics and one indonesian language  lectures.The practicalities of data taken using qustion form and interview.Data analyzed with tecniques and processed in a descriptive  percentage.the result showed that the learning interactive CD media using macromedia flash  on the material of the cube for grade VIII SMP/MTs has a very valid and validity suggest that interactive CD have been practical because of time, use and benefits of the CD had been in accordance.